Analisis Komparasi Distribusi Keuntungan Penjualan Gabah dan Beras di Kabupaten Musi Rawas - Ira Primalasari; Vera Octalia (Yayasan Literasi Sains Indonesia, 2025)
Musi Rawas Regency is one of the regencies that has experienced significant growth in agriculture, especially rice. The choice to sell in the form of grain or rice is a strategic decision for farmers because it concerns production efficiency, potential profits, and risks that must be faced. This study aims to provide a comparative analysis quantitatively and qualitatively of both forms of sales, including considering cost factors, distribution models and supporting institutions in Musi Rawas Regency. The determination of the farmer sample in this study used purposive random sampling of 75 people. The data sources in this study used primary and secondary data The research results show that selling unhusked rice is more profitable for farmers if done directly, with a 100% profit margin (farmer to Bulog). Unhusked rice sales are more profitable because they don't require post-harvest activities. This differs from selling rice, which requires post-harvest handling and therefore incurs costs. There are three profit comparison models for rice sales: 70%/30%, 50%/50%, and 30%/70%. The largest marketing margin is located in marketing channel 1, with a total margin of Rp 5,300, while the smallest total margin is in marketing channel 3, namely Rp 2,000. From the analysis results, it is known that the marketing margin of agricultural products is influenced by the number of marketing institutions involved, transportation costs. High margins do not necessarily indicate inefficiency, but may reflect the high operational costs and risks borne by intermediaries.